Parallel computational fluid dynamics advanced numerical methods : software and applications : proceedings of the Parallel CFD 2003 Conference, Moscow, Russia (May 13-15, 2003) - Parallel CFD Conference (2003 : Moscow, Russia); Chetverushkin, B. N. (Boris Nikolaevich) (Amsterdam : Elsevier, 2004)
The book is devoted to using of parallel multiprocessor computer systems for numerical simulation of the problems which can be described by the equations of continuum mechanics. Parallel algorithms and software, the problems of meta-computing are discussed in details, some results of high performance simulation of modern gas dynamic problems, combustion phenomena, plasma physics etc are presented. Parallel Algorithms for Multidisciplinary Studies.
Contents -- Preface. -- Acknowledgements. -- 1. Invited Papers -- 2. Numerical Methods And Parallel Algorithms -- 3. Turbulence And Acoustics Problems -- 4. Combustions Problems -- 5. Metacomputing And Grid Technologies -- 6. Environment and Ecology Problems -- 7. Plasma And Kinetics Problems -- 8. Parallel Software -- 9. Heat And Mass Transfer Problems -- 10. Aerodynamic And Hydrodynamic Flows.
Includes bibliographical references.
Keywords: Fluid dynamics -- Data processing -- Congresses; Parallel processing (Electronic computers) -- Congresses; Parallel CFD Conference / (2003 / Moscow, Russia); Electronic books